Enterococcus Faecalis Endocarditis Following Percutaneous Manipulation of a Biliary Tract Calculus and ERCP - Allan R Ronald; Andrew LS Pattullo (Canadian Journal of Infectious Diseases)
A case of Enterococcus faecalis endocarditis followed endoscopic retrograde cholangiopancreatography and percutaneous extraction of a biliary calculus is reported. The most likely cause of endocarditis, though unproven, is the latter procedure, as the bile is often infected during biliary tract obstruction, and bacteremia is frequent during percutaneous manipulations. Initial therapy with vancomycin was unsuccessful in clearing the bacteremia, possibly due to vancomycin tolerance of the isolate and lack of an aminoglycoside in the initial regimen. Cure was obtained when therapy with ampicillin and gentamicin was undertaken.